An Arabidopsis TIR-Lectin Two-Domain Protein Confers Defense Properties against Tetranychus urticae. Issue 4 (14th February 2019) - Santamaría, M. Estrella; Martínez, Manuel; Arnaiz, Ana; Rioja, Cristina; Burow, Meike; Grbic, Vojislava; Díaz, Isabel
Abstract : PP2-A5 is an Arabidopsis TIR-lectin two-domain protein that confers defense properties against Tetranychus urticae by affecting gene expression and hormonal signaling. Abstract: Plant immunity depends on fast and specific transcriptional reprogramming triggered by the perception of biotic stresses. Numerous studies have been conducted to better understand the response of plants to the generalist herbivore two-spotted spider mite ( Tetranychus urticae ). However, how plants perceive mites and how this perception is translated into changes in gene expression are largely unknown. In this work, we identified a gene induced in Arabidopsis ( Arabidopsis thaliana ) upon spider mite attack that encodes a two-domain protein containing predicted lectin and Toll/Interleukin-1 receptor domains. The gene, previously named PP2-A5, belongs to the Phloem Protein2 family. Biotic assays showed that PP2-A5 confers tolerance to T. urticae . Overexpression or knockout of PP2-A5 leads to transcriptional reprogramming that alters the balance of hormone accumulation and corresponding signaling pathways. The nucleocytoplasmic location of this protein supports a direct interaction with regulators of gene transcription, suggesting that the combination of two putative signaling domains in a single protein may provide a novel mechanism for regulating gene expression. Together, our results suggest that PP2-A5 improves the ability to defend against T. urticae by participating in the tight regulation of hormonal cross talk upon mite feeding. Further research is needed to determine the mechanism by which this two-domain protein functions and to clarify its molecular role in signaling following a spider mite attack.